On the Interpretation of Giving in Dictator Games - List, John A. (Journal of Political Economy, 2007)
The dictator game represents a workhorse within experimental economics, frequently used to test theory and to provide insights into the prevalence of social preferences. This study explores more closely the dictator game and the literatureâ€™s preferred interpretation of its meaning by collecting data from nearly 200 dictators across treatments that varied the action set and the origin of endowment. The action set variation includes choices in which the dictator can â€œtakeâ€ money from the other player. Empirical results question the received interpretation of dictator game giving: many fewer agents are willing to transfer money when the action set includes taking. Yet, a result that holds regardless of action set composition is that agents do not ubiquitously choose the most selfish outcome. The results have implications for theoretical models of social preferences, highlight that â€œinstitutionsâ€ matter a great deal, and point to useful avenues for future research using simple dictator games and relevant manipulations.